Detection and molecular characterisation of Giardia duodenalis, Cryptosporidium spp. and Entamoeba spp. among patients with gastrointestinal symptoms in Gambo Hospital, Oromia Region, southern Ethiopia. Issue 9 (19th May 2015) - Flecha, María J.; Benavides, Cynthia M.; Tissiano, Gabriel; Tesfamariam, Abraham; Cuadros, Juan; de Lucio, Aida; Bailo, Begoña; Cano, Lourdes; Fuentes, Isabel; Carmena, David
Summary Objectives To assess the prevalence and genetic diversity of the enteric protozoa species G. duodenalis, Cryptosporidium spp. and Entamoeba histolytica in individuals with gastrointestinal symptoms compatible with infections by these pathogens seeking medical attention in a rural area in southern Ethiopia. Methods A total of 92 stool samples were initially screened by direct microscopy and immunochromatography and further confirmed by molecular methods. G. duodenalis‐positive samples were molecularly characterised by multilocus genotyping of the glutamate dehydrogenase and β‐giardin genes of the parasite. PCR and DNA sequence analysis of the gene encoding the 60‐kDa glycoprotein was used for the subtyping of Cryptosporidium isolates. Detection and differential diagnosis of E. histolytica/dispar were conducted by real‐time PCR. Results PCR‐based prevalences were 10.9% for G. duodenalis, 1.1% for Cryptosporidium spp. and 3.3% for Entamoeba spp. Seven (four novel and three known) subtypes of G. duodenalis assemblage B were identified at the GDH locus and 5 (one novel and four known) at the BG locus. A novel variant of C. hominis subtype IbA9G3 was also identified. Two Entamoeba isolates were assigned to E. dispar and an additional one to E. histolytica. Conclusion Although preliminary, our results strongly suggest that giardiasis, cryptosporidiosis and amoebiasis represent a significant burden in Ethiopian rural population.